2021
DOI: 10.3390/su13116021
|View full text |Cite
|
Sign up to set email alerts
|

How Brand Symbolism, Perceived Service Quality, and CSR Skepticism Influence Consumers to Engage in Citizenship Behavior

Abstract: Brand symbolism, which stems from the vitality of the brand and feeds self-symbolism and social symbolism, has become an increasingly important strategy for firms to enhance consumer behavior. Building on attachment theory, social identity theory, and cognitive consistency theory, and using data from 439 customers of Starbucks in Lebanon, we used an integrative model to examine how brand symbolism, perceived service quality, and Corporate Social Responsibility (CSR) skepticism jointly affect two types of Custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 94 publications
1
3
0
Order By: Relevance
“…Our findings revealed that consumers' perceptions about retailers commitment to CSR could improve customer citizenship behaviour. These findings corroborate the widely held belief (Dalal and Aljarah, 2021;Kim et al, 2020;Mohammad Shafiee and Tabaeeian, 2021;Nguyen and Pervan, 2020) that CSR has a significant effect on customer citizenship behaviour. This implies that the more activities a retailer is seen to be involved in, such as establishing a fair pricing policy and generating employment, the greater its CCB.…”
Section: Key Findingssupporting
confidence: 90%
“…Our findings revealed that consumers' perceptions about retailers commitment to CSR could improve customer citizenship behaviour. These findings corroborate the widely held belief (Dalal and Aljarah, 2021;Kim et al, 2020;Mohammad Shafiee and Tabaeeian, 2021;Nguyen and Pervan, 2020) that CSR has a significant effect on customer citizenship behaviour. This implies that the more activities a retailer is seen to be involved in, such as establishing a fair pricing policy and generating employment, the greater its CCB.…”
Section: Key Findingssupporting
confidence: 90%
“…Until recently, previous studies have concentrated only on the direct effect of CSR on customer citizenship behavior (Dalal & Aljarah, 2021; Kim & Kim, 2018) or the simple mediating impact of variables such as brand attachment and brand image (Hur et al, 2020). Therefore, this study investigated the relationship between CSR and customer citizenship behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a client must establish an emotional connection with a brand to engage with it on social media (Taiminen & Ranaweera, 2019). Attachment is the strong emotional connection consumers have with specific brands that prevents them from moving to other products and creates more enduring relationships between consumers and companies (Taiminen & Ranaweera, 2019;Dalal & Aljarah, 2021). There are three types of attachment: social structure, relationship, and identity attachment (Ghorbanzadeh & Rahehagh, 2021).…”
Section: Theoretical Review Attachment Theorymentioning
confidence: 99%